Livera, Andreas - (:unkn) unknown (My University, 2026)
Dr Andreas Livera received his BSc and PhD in Electrical Engineering from the University of Cyprus (UCY) in 2015 and 2022, respectively. Andreas was also awarded a scholarship from Cyprus State Scholarships Foundation for master’s studies in Sustainable Energy Futures at Imperial College London (UK) in 2016. During his studies, he was awarded several prestigious awards (Technical Chamber of Cyprus Engineering Award 2020 - given to one engineer in Cyprus every three years) and grants (2022 PRE-SEED by Research and Innovation Foundation of Cyprus and ITC conference grant by the COST Action 2019). He has been working as a researcher at the UCY since 2017 in the field of fault diagnostics for photovoltaic (PV) systems. He has a deep knowledge of machine learning principles, and his research interests lie in studying and improving solar-plus-storage system’s performance and reliability through the development of image- and data-driven software algorithms. He has authored and co-authored more than thirty five publications in the field of solar energy. He is also a member of the Technical Chamber of Cyprus and of the Electromechanical Chamber of Cyprus and a certified PV installer and designer.